PENGETAHUAN, SIKAP DAN KESIAPAN SISWI SEKOLAH DASAR ISLAM DI SURAKARTA DALAM MENGHADAPI MENARCHE - Dyah Rahmawatie Ratna Budi Utami; Wahyuni; Yuwita Aulia Rachma Wardani (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2022)
Menarche is the first menstruation and is a marker for young women entering puberty. The average age of menarche for girls occurs in the range of 9-15 years. Lack of knowledge and negative attitudes related to menstruation will affect the readiness of students to face menarche. The objectives of this study were to identify the level of knowledge, attitudes, and readiness of students to face menarche and analyze the relationship between knowledge and attitudes towards readiness to face menarche at Ta'mirul Islam Elementary School Surakarta. This type of research is descriptive-analytic with a cross-sectional design, the sample in this study was 83 respondents. The sampling technique used purposive sampling. The research instrument used a knowledge, attitude, and readiness questionnaire. Informed consent was obtained from parental consent. Data analysis to answer the hypothesis using the chi-square analysis technique. The results of the univariate analysis showed that children's knowledge was sufficient (34.9%), positive attitude (74.04% of children), and 75.9% of readiness stated that they were ready to face menarche. The results of the bivariate analysis showed that there was a significant relationship between knowledge and readiness to face menarche and there was a significant relationship between attitudes and readiness to face menarche with a p-value <0.001. There is a relationship between knowledge and attitudes of SD Takmirul Islam students with readiness to face menarche.